2020
DOI: 10.1108/rjta-01-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cotton parameters on sensorial comfort of woven fabrics

Abstract: Purpose For cloths having direct contact with the skin, comfort properties are a priority than the physical and mechanical properties. Innerwear clothes should induce pleasant feelings because they have a direct influence on human psychological satisfaction, health and work efficiency. The purpose of this study is to investigate the impact of cotton fiber parameters on the sensorial comfort of woven fabrics. Design/methodology/approach Four types of cotton fiber with different fineness, mean length, uniformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Thus, it can be concluded that the fabric had a larger RC in the coursewise in comparison with the walewise. In line with this relationship, a recent study proved that fibre elongation has a direct influence on the RC factor [ 37 ], while others reported that elastic recovery for a knit structure occurs more strongly in the coursewise direction in comparison to the walewise direction [ 38 ]. However, the yarn direction is not relevant anymore at amounts of GNPs above 10%.…”
Section: Resultsmentioning
confidence: 82%
“…Thus, it can be concluded that the fabric had a larger RC in the coursewise in comparison with the walewise. In line with this relationship, a recent study proved that fibre elongation has a direct influence on the RC factor [ 37 ], while others reported that elastic recovery for a knit structure occurs more strongly in the coursewise direction in comparison to the walewise direction [ 38 ]. However, the yarn direction is not relevant anymore at amounts of GNPs above 10%.…”
Section: Resultsmentioning
confidence: 82%
“…77 Finally, the blends of cotton and flax fiber were found to have lower bending rigidity values than flax fiber. 19,23,76…”
Section: Resultsmentioning
confidence: 99%
“…77 Finally, the blends of cotton and flax fiber were found to have lower bending rigidity values than flax fiber. 19,23,76 The washing treatments were also found to be influential on the bending length and rigidity values. Considering that low bending rigidity is preferred to achieve softness, the treated samples had a better handle.…”
Section: Tactile Comfortmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the performance of layered fabrics in thermo-physiological regulation is better than that of single-layer textile structures [11][12][13][14]. Several researchers have investigated the influence of fiber fineness and cross-sectional shapes [15,16] as well as the effects of fiber type, stitch type [17,18], yarn type [19], fabric structure [20][21][22][23][24], bi-layer fabrics [25][26][27], multi-layer sportswear [28,29], blended fabric [30,31], and 2D and 3D designs of sportswear [17,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%